2017
DOI: 10.1080/13621718.2016.1183079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heat input during friction stir welding of aluminium alloys

Abstract: Heat input is one of the key parameters governing the quality and service properties of friction stir welds. By using a calorimetric technique, the heat inputs generated during the friction stir welding of the aluminium alloys, 1100 and 5083, were measured over a wide range of welding parameters. An empirical equation to estimate the heat input using the welding parameters was established based on a multiple regression analysis of the results. The effect of the heat input on the final grain size of the stir zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…8 and only the samples subjected to a single type of aging (NA) were reported because no differences in grain size were observed after the post-welding heat treatment. Therefore, similar maximum temperatures reached in the NZ and the negligible effect of different cooling times on the NZ grain size can be confirmed, as already reported by [23]. Also, the differences in maximum temperature measured between TC 1 and TC 2 are around 20 • C and 50 • C for joints made at 60 mm/min and 180 mm/min, respectively.…”
Section: Temperature Measurementssupporting
confidence: 89%
See 1 more Smart Citation
“…8 and only the samples subjected to a single type of aging (NA) were reported because no differences in grain size were observed after the post-welding heat treatment. Therefore, similar maximum temperatures reached in the NZ and the negligible effect of different cooling times on the NZ grain size can be confirmed, as already reported by [23]. Also, the differences in maximum temperature measured between TC 1 and TC 2 are around 20 • C and 50 • C for joints made at 60 mm/min and 180 mm/min, respectively.…”
Section: Temperature Measurementssupporting
confidence: 89%
“…In addition, extra information can be gathered by estimating the different heat inputs obtained in the various configurations. The heat input was calculated using the empirical model proposed by [23] (1). HI = 7.8 v −0.80 ω 0.10 D 0.55…”
Section: Temperature Measurementsmentioning
confidence: 99%
“…Furthermore, the heat input per unit length for both speed levels converges with increasing traverse speed with differences of 89 J/mm for 100 mm/min, 63 J/mm for 150 mm/min, 41 J/mm for 200 mm/min, and 34 J/mm for 250 mm/min. Both effects are characteristical for FSW processes [5,21].…”
Section: Sensitivity Analysis Of Process Forcesmentioning
confidence: 99%
“…The authors found smaller grain size in the nugget zone for the welds performed at 48 mm/min compared to the one manufactured at 18 mm/min, employing the same rotational speed. Overall, the influence of the most influential weld parameters, namely feed rate and rotational speed, on the microstructural refinement during FSW has been properly summarized by Yi et al [40]. The authors claimed that the grain size in the nugget zone during FSW is firstly influenced by the rotational speed, that affects the peak temperature, and then by the feed rate, that affects the rate of the cooling cycle.…”
Section: Introductionmentioning
confidence: 99%